Energy Generation by Extracellular Aldose Oxidation in N(2)-Fixing Gluconacetobacter diazotrophicus - Luna, María F. (American Society for Microbiology, 2002)
Gluconacetobacter diazotrophicus PAL3 was grown in a chemostat with N(2) and mixtures of xylose and gluconate. Xylose was oxidized to xylonate, which was accumulated in the culture supernatants. Biomass yields and carbon from gluconate incorporated into biomass increased with the rate of xylose oxidation. By using metabolic balances it is demonstrated that extracellular xylose oxidation led N(2)-fixing G. diazotrophicus cultures to increase the efficiency of energy generation.